2022
DOI: 10.1002/emp2.12678
|View full text |Cite
|
Sign up to set email alerts
|

A pilot mixed‐methods randomized controlled trial of verbal versus electronic screening for adverse social determinants of health

Abstract: Objectives: Examining the social risks that influence the health of patients accessing emergency care can inform future efforts to improve health outcomes. The optimal modality for screening in the emergency department (ED) has not yet been identified. We conducted a mixed methods evaluation of the impact of screening modality on patient satisfaction with the screening process. Methods:Patients were enrolled at a large urban academic ED and randomized to verbal versus electronic modalities following informed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…To power a trial to detect 4% difference in disclosure would require > 1200 participants (alpha 5%, power 80%). Similarly, our qualitative findings about the acceptability of screening are consistent with other US-based studies involving screening [ 19 , 20 ]. It is difficult to compare the current findings with European and UK contexts, as those studies commonly occur in primary care where populations, screening and referral workflows differ to inpatient settings.…”
Section: Discussionsupporting
confidence: 90%
“…To power a trial to detect 4% difference in disclosure would require > 1200 participants (alpha 5%, power 80%). Similarly, our qualitative findings about the acceptability of screening are consistent with other US-based studies involving screening [ 19 , 20 ]. It is difficult to compare the current findings with European and UK contexts, as those studies commonly occur in primary care where populations, screening and referral workflows differ to inpatient settings.…”
Section: Discussionsupporting
confidence: 90%
“…Six screening tools were administered to pediatric patients [ 27 , 29 31 , 37 , 47 ]. One was designed to assess pregnant patients [ 34 ], and the remaining tools ( n = 18) were utilized for general screening purposes in clinical settings, such as hospitals or clinical offices [ 13 , 25 , 26 , 28 , 32 , 33 , 35 , 36 , 38 – 46 , 48 – 53 ] Six tools were administered by healthcare professionals [ 13 , 25 , 30 , 32 , 46 , 49 ]; while 12 tools were completed by patients (or parents) either electronically or on paper [ 13 , 28 , 29 , 34 , 36 , 37 , 44 , 45 , 47 , 48 , 50 , 52 ]; six tools were administered verbally or were self-administered at the patient’s request [ 26 , 27 , 31 , 33 , 35 , 53 ]; The number of questions in any given SDoH assessment tool varied considerably and ranged from 5 in Health Leads (2018) and the North Carolina toolkit [ 36 ], as well as the Core 5 social risk tool [ 28 ] to 50 in the health system’s EPIC electronic health records screening tool [ 33 ]; overall, the mean number of questions in any given SDoH screening tool assessment was 16.6 (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six screening tools were administered to pediatric patients [27,[29][30][31]37,47]. One was designed to assess pregnant patients [34], and the remaining tools (n = 18) were utilized for general screening purposes in clinical settings, such as hospitals or clinical offices [13,25,26,28,32,33,35,36,[38][39][40][41][42][43][44][45][46][48][49][50][51][52][53] Six tools were administered by healthcare professionals [13,25,30,32,46,49]; while 12 tools were completed by patients (or parents) either electronically or on paper [13,28,29,34,36,37,44,45,47,48,50,52]; six tools were administered verbally or...…”
Section: Screening Tools Characteristicsmentioning
confidence: 99%
“…In-person HRSN screening and referral faces multiple challenges, including funding/sustainability; staff availability, training, and bias; and universal application, making digital modalities an attractive, light touch option [ 25 ]. Pediatric and adult studies have demonstrated similar or even greater patient/family HRSN disclosure, acceptability, and comfort with tablet-based screening compared to that of face-to-face, likely due to perceived screening anonymity [ 5 , 6 , 13 , 26 ]. There is currently no clear recommendation for screening and referral modality, although in general, social risk screening itself has been shown to be widely acceptable by patients/families [ 13 , [26] , [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric and adult studies have demonstrated similar or even greater patient/family HRSN disclosure, acceptability, and comfort with tablet-based screening compared to that of face-to-face, likely due to perceived screening anonymity [ 5 , 6 , 13 , 26 ]. There is currently no clear recommendation for screening and referral modality, although in general, social risk screening itself has been shown to be widely acceptable by patients/families [ 13 , [26] , [27] , [28] , [29] ]. While our study demonstrated family preference for digital means of reporting and receiving HRSN information, it is important from a health equity standpoint to include alternative written means for those who may not have access to a smartphone or computer.…”
Section: Discussionmentioning
confidence: 99%